B cell-helping functions of gut microbial metabolites - Chang H. Kim (Microbial Cell, 2016)
Commensal microflora profoundly affects the host immune system. It has long been observed that commensal bacteria enhance antibody production in the host by producing antigens for B cell receptors (BCR) and ligands for Toll-like receptors (TLR). We recently reported that the microbial metabolites short-chain fatty acids (SCFAs) regulate the metabolism and gene expression in B cells to promote antibody production (Kim et al. Gut Microbial Metabolites Fuel Host Antibody Responses. Cell Host & Microbe. 2016; 20(2):202-14). The B-cell helping function of SCFAs and its implication in the host immune system are discussed in this article.